Exploring the role of the microbiome in inflammatory arthritis disease pathogenesis - Brough, I (2023)
Spondyloarthritis (SpA) is characterised by chronic, destructive joint inflammation and in many patients, intestinal inflammation. Microbiome profiling in SpA has identified increased abundances of inflammation-associated bacteria, and patients with reactive arthritis (ReA); a subset of SpA, develop joint inflammation following gastrointestinal (GI) infection. Despite the presence of these microbiome associations, the host-microbe interactions supporting disease remain largely unknown and may provide an avenue for microbiota-based therapies. The SKG mouse model of SpA develops microbiota-dependent joint and intestinal inflammation following dectin-1 activation with curdlan. Thus, in this thesis we aimed to study two forms of SpA; ReA and axial spondyloarthritis (AxSpA) in the SKG mouse model to delineate the host-microbe interactions driving joint disease. Firstly, we developed a microbiota-dependent model for ReA utilising GI infection with a murine enteropathogen in place of curdlan and characterised the microbiome and the T cell responses in this model. Secondly, we leveraged gnotobiotic SKG mice to delineate host-microbe interactions driving disease in the SKG-curdlan model. We found that although germ-free SKG mice did not develop disease, monocolonisation followed by depletion of the bacterium Bifidobacterium animalis did not prevent onset of disease. Furthermore, administration of heat-killed B. animalis to germ-free SKG mice enabled the induction of joint disease, suggesting that a component of B. animalis programs the host immune system to respond to curdlan and trigger disease. Finally, to determine the clinical relevance of studying the intestinal microbiome in SpA we completed immune phenotyping on AxSpA blood and stool, as well as stool metabolomic analysis. We identified a Th17 signature in the stool and blood of patients with AxSpA and identified several stool amino acids negatively associated with stool IL-23, suggesting an association between the host immune system and amino acid availability to microbes. Collectively, this work identifies several host-microbe associations in murine models of SpA as well as in patients with SpA and opens new avenues for the exploration of the host-microbe interactions supporting disease in SpA.